Peroxiredoxin IV protects cells from oxidative stress by removing H(2)O(2) produced during disulphide formation - Tavender, Timothy J. (Company of Biologists, 2010)
Disulphide formation within the endoplasmic reticulum (ER) requires the activity of the ER oxidase Ero1, and as a consequence, generates hydrogen peroxide. The production of hydrogen peroxide is thought to lead to oxidative stress that ultimately results in apoptosis. Here, we show that mammalian peroxiredoxin IV (PrxIV) metabolises hydrogen peroxide produced by Ero1. We demonstrate that the presence of PrxIV within the ER provides a cytoprotective effect against stresses known to enhance Ero1 activity and perturb ER redox balance. Increased Ero1 activity and production of hydrogen peroxide led to preferential hyperoxidation of PrxIV relative to peroxiredoxins in other cellular compartments. The hyperoxidation was increased by the upregulation of Ero1 and by the expression of a hyperactive Ero1. These findings provide the first evidence for an enzymatic mechanism that facilitates peroxide removal from the ER, and show that the oxidation status of PrxIV acts as a marker for ER oxidative stress.